The effect of a training methodology with different courts on the accuracy and speed of motor response of forehand strokes in wheelchair tennis age groups - Hussein Alawi, Karima (sports creativity, 2025)
The level of performance in tennis has risen significantly in recent years, and efforts to improve skill and speed have noticeably increased worldwide. Tennis is a sport that relies heavily on speed and a variety of playing styles. Therefore, training programs must focus on speed in general, and on the accuracy of reaction time and precision in particular, along with the associated physical and mental demands. This requires players to exert appropriate effort to develop their skills and reaction time through specialized training programs using both hard and clay courts, which are the surfaces on which tournaments are held. Tennis is a fast-paced sport with diverse movements and a high level of motor skills. Some skills can reach speeds exceeding 240 km/h, and this high speed demands rapid reactions, especially on hard courts, in addition to precision. Reaction time is one of the most important attributes contributing to success in most sports that rely on speed, change of direction, and surprise, particularly in wheelchair tennis, which is characterized by its diverse and rapid skills, especially the forehand, backhand, and serve. The forehand stroke is one of the most important and frequently used skills during a match, and it must be mastered completely to achieve success. Its frequent use and complete mastery contribute to a well-rounded tennis performance, especially for wheelchair tennis players. A player's development depends largely on proficiency in using the forehand stroke in its various forms, while also not neglecting other strokes. Therefore, this research is important, especially given the scarcity of previous field studies addressing this issue in tennis or exploring its various dimensions. This prompted the researcher to conduct this scientific study.